Determination of copper in fish feed by graphite furnace atomic absorption spectrometry using slurry sampling - Neves, Renato C.F. [UNESP]; Moraes, Paula M. [UNESP]; Silva, Fábio A. [UNESP]; Loureiro, Vanessa R. [UNESP]; Saleh, Mayra A.D. [UNESP]; Padilha, Cilene C.F. [UNESP]; Barros, Margarida Maria [UNESP]; Padilha, Pedro de Magalhães [UNESP] (Springer Nature, 2008)
The present work develops and optimizes a method to determine copper in samples of feces and fish feed by graphite furnace atomic absorption spectrometry (GFAAS) through the direct introduction of slurries of the samples into the spectrometer's graphite tube coated internally with metallic rhodium and tungsten carbide that acts as chemical modifiers. The limits of detection (LOD) and quantification (LOQ) calculated for 20 readings of the blank of the standard slurries (0.50% m/v of feces or feed devoid of copper) were 0.24 and 0.79 μg L -1 for the standard feces slurries and 0.26 and 0.87 μg L -1 for the standard feed slurries. The proposed method was applied in studies of absorption of copper in different fish feeds and their results proved compatible with that obtained from samples mineralized by acid digestion using microwave oven. © Springer Science+Business Media, LLC 2008.
Keywords: Copper determination; Fish feed; GFAAS; Slurries samples; Acid digestions; Atomic absorptions; Chemical modifiers; Feed slurries; Fish feeds; Graphite furnaces; Graphite tubes; Limits of detections; Slurry samplings; Absorption; Atomic absorption spectrometry; Atomic physics; Atomic spectroscopy; Atoms; Copper; Fish; Furnaces; Graphite; Meats; Microwave devices; Microwave ovens; Rhodium; Slurries; Spectrometers; Spectrometry; Standards; Stoves; Tungsten; Tungsten carbide; Absorption spectroscopy